Strontium hydroxyapatite in situ gel‐forming system – a new approach for minimally invasive bone augmentation. Issue 5 (9th July 2014) - Hao, J.; Chou, J.; Kuroda, S.; Otsuka, M.; Kasugai, S.; Lang, N. P.
Abstract Objectives To achieve ideal functional and aesthetic requirements, ridge augmentation is often required before dental implant placement. Bone augmentation (especially vertical), which normally consists of complex and invasive surgeries, still remains challenge. This study seeks to investigate the feasibility of an injectable in situ gel‐forming system containing strontium hydroxyapatite (SrHA) and alginate for minimally invasive bone augmentation in a rat calvarial model. Material and methods SrHA–alginate solution was prepared by mixing SrHA powder with alginate solution (20 mg/mL) to the final concentration of 0.5% (w/v). Each animal received a 200‐μL single subperiosteal injection of either SrHA–alginate solution or alginate solution. The new bone formation was assessed at 0, 4, and 8 weeks histologically and radiologically. Results The SrHA–alginate solution materials could form solid gel once injected. As such, no sutures were required to close the injection site. Significantly greater amount of new bone formation was observed in the SrHA–alginate group compared with the alginate group both by micro‐CT and by histological section. The newly formed bone in the SrHA–alginate group originated both from the underlying original bone and from the elevated periosteum. A 2.3‐fold increase of the vertical bone height was observed in the SrHA–alginate group compared with 1.3‐fold increase in the alginate group. Conclusions Rat calvarial bone augmentation was achieved by a single subperiosteal injection of SrHA–alginate solution without any administration of stem cells or growth factors. The in situ gel‐forming material may hold potential therapeutic benefits for local bone augmentation in a minimally invasive manner.